Eco-efficient mortars with incorporation of phase change materials - Cunha, S. (2018)
Nowadays, the construction is one of the main European sectors responsible for the high levels of energy consumption and raw material extraction. Increasingly, the energy consumption from renewable sources and industrial waste reuse are the only ways to minimize these environmental and societal problems. Simultaneous incorporation of phase change materials and fly ash in the mortars increases the energy efficiency and decreases the waste materials landfilled. The development of mortars with phase change materials and fly ash incorporation contributes to a significant improvement of the building comfort parameters and the environmental quality. The phase change materials possess the capability to normalize the temperature flux inside the buildings, using the solar energy as resource. The main purposes of this study were the physical, mechanical, and thermal characterization of mortars with phase change materials and fly ash incorporation. It was concluded that the phase change materials and fly ash simultaneous incorporation leads to homogeneous and suitable mortars with increased thermal behavior compared with the phase change material addition alone.